2007
DOI: 10.1111/j.1467-9396.2007.00667.x
|View full text |Cite
|
Sign up to set email alerts
|

International Productivity Differences, Infrastructure, and Comparative Advantage*

Abstract: This paper provides an empirical analysis of the effect of infrastructure provision on industry-level productivity and international specialization, as suggested by Clarida and Findlay's (1992 ) model. We calculate total factor productivity (TFP) for 18 developed and developing countries and 10 manufacturing industries, and study the effects of supplies of roads, telecommunications and electric power on international variations in sectoral TFP, i.e. comparative advantage. We also examine the effects of infrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
68
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(76 citation statements)
references
References 17 publications
0
68
0
1
Order By: Relevance
“…Yeaple and Golub (2007) study the effect of the infrastructure investment on ten different industrial sectors, and find that increased provision of infrastructure helps to explain patterns of international specialization and trade. Mbekeani (2010) suggests that inadequate infrastructure and poor transport organization in Africa hinder the timely delivery reliability in the supply of goods.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Yeaple and Golub (2007) study the effect of the infrastructure investment on ten different industrial sectors, and find that increased provision of infrastructure helps to explain patterns of international specialization and trade. Mbekeani (2010) suggests that inadequate infrastructure and poor transport organization in Africa hinder the timely delivery reliability in the supply of goods.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous studies that analyzed the relationship between trade and infrastructure have found a positive and significant impact of infrastructure on trade (Limão and Venables, 2001;Nordäs and Piermartini, 2004;Yeaple and Golub, 2007). Focusing on the increasing public-private partnerships, the aim of this paper is to analyze the relationship between public-private investments in infrastructure on the agricultural exports of developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…Chakraborty and Nandi (2011); Khandker and koolwal (2011) argued that the impact of the procurement of transport and communication infrastructure is a topic that has attracted considerable attention in the literature along the few last years. Yeaple, and Golub (2007) say that the transport infrastructures have the greatest potential to stimulate the economy in the long-run. In addition, several economists affirm that there is no doubt that there is a strong linkage between investments in transport infrastructures and economic productivity.…”
Section: Severalmentioning
confidence: 99%
“…To demonstrate the role of road transport in the development of economic activity, Yeaple, and Golub (2007) present their study for 12 developed and developing countries. In their study, they estimated the effects of three types of infrastructure (roads, telecommunications, and electricity) on total factor productivity in 10 industrial sectors between 1979 and 1997.…”
Section: Severalmentioning
confidence: 99%
See 1 more Smart Citation